Digital preaching activity: A critical perspective of the public relations - Jauhari, Minan; Maghfiroh, Eva; Hayyan Najikh, Ahmad (SHAHIH: Journal of Islamicate Multidisciplinary, 2023)
This article positions the "Muslimah Media Center" (MMC) as the Islamic digital preaching activities. This religious community media identifies itself as an Islamic platform with a commitment to propagating Islamic values. It actively presents content analyzing various Islamic issues and often campaigns for Islam as a practical and effective solution to every problem. The portrayal of religious reality presented in the digital space plays a significant role in shaping the image of Islam in the virtual world. Hence, there is a need for an investigation into digital preaching activism that shapes the image of Islam, employing a Critical Public Relations (PR) perspective. The objective is to provide a critical and explorative explanation to understand how Islamic performance is showcased through the Muslimah Media Center. This study uses virtual ethnography as its method, as the data collected is sourced from digital traces and artifacts. Consequently, it can be concluded that the image of Islam generated by this digital preaching activism not only reinforces religious beliefs but also disseminates certain ideologies that are assumed to be in contrast with other religious ideologies.